Iron/Iron Carbide (Fe/Fe3C) Encapsulated in S, N Codoped Graphitic Carbon as a Robust HER Electrocatalyst - Jaiswal A.; Kumar R.; Prakash R. (My University, 2025)
In the present work, iron carbide (Fe/Fe3C) encapsulated in sulfur and nitrogen codoped graphitic carbon was synthesized using a low-cost, one-step pyrolytic method. The as-prepared nanomaterials were investigated for catalytic hydrogen evolution reaction (HER) in acidic medium. Doping of sulfur and nitrogen was achieved by adding different weights of thiourea along with ferrocene and toluene precursors. X-ray photoelectron spectroscopy and energy-dispersive X-ray spectroscopy verify the presence of sulfur and nitrogen species in the synthesized material. It is found that a small and optimum amount (10 and 20 wt %) of thiourea addition leads to significant enhancement in the number of active sites, which leads to a many-fold increase in current density for the prepared samples. Among the synthesized samples, Fe@C-SN/25 and Fe@C-SN/50 exhibit robust catalytic performance with overpotential values of 518 and 536 mV @ 10 mA cm-2, respectively, while an optimum S, N codoped graphitic carbon-Fe/Fe3C (Fe@C-SN/50) shows the lowest onset potential of 372 mV among its others counterparts, for a catalyst loading of 0.554 mg cm-2. © 2021 American Chemical Society.